Peptide-Based Drugs: Development and Therapeutic Applications - Kanojia, Akanksha; Singh, Shekhar; Rai, Vishal; Yadav, Ajay (Journal for Research in Applied Sciences and Biotechnology, 2024)
Current advances in knowledge about peptides as drugs are of great significance; They have planning potentialities in different sections of medicinal practice. This review will summarize the progress in the synthesis and the biological activities of the peptide-based drug, along with some of the uses. We start with the historical aspect and key points in the development of the corresponding field. In general, the development part describes the approaches of peptides synthesis, design strategies, screening methods, and optimization for stability and bioavailability. We then describe the action of such mechanisms as with respect to receptors, enzymes, and peptides that can penetrate cells. It has also expanded the assessment of the description of peptide drugs in the treatment of cancer, cardiovascular diseases, metabolic diseases, neurological diseases, infectious diseases, and immunotherapy. We cover both the problems in the formation of peptide drugs like stability, delivery, and regulatory issues and the opportunities like nanotechnology, bioprinting, and CRISPR. Last, we discuss the outlook of the peptide-based therapeutics and review features, which are promising for the development of new trends and perspectives of application. The present review is intended to give an up-to-date and easy to grasp information regarding the status and perspectives of peptide-associated medicines in contemporary pharmacology.